Gamification and game-based learning: strategies to promote positive competitiveness in the teaching and learning processes - Barradas, Rolando (2021)
This chapter presents a study carried out within the Supervised Teaching Practice of the Masters’ Degree in Informatics Teaching at the University of Minho. It seeks to identify the reason for the integration of games and gamification to promote positive competitiveness of vocational training students. To address this goal, we have designed six challenges that seek to focus the student on the learning process and respond to the following research question: Are gamification and game-based learning the right strategies to promote positive competitiveness in teaching and learning processes?